Supplementation of Skipjack Roe Protein Concentrate (RPC) Into Breastfeeding Complimentary Foods - Frets Jonas Rieuwpassa; Joko Santoso; Wini Trilaksani (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Protein malnutrition in toddler is a problematic issue in Indonesia. Inclusion of roe protein concentrate (RPC) from skipjack in the breastfeeding complimentary foods of or infant foods can be an alternative to solve the protein malnutrition. This research was aimed to analyze the organoleptic score, nutritional facts and functional properties of the infant food supplemented with the RPC. Six different formulations (F1-F6) were prepared. The F2 formula was considered as the best formula. The infant food prepared using this formula contained 19.43% of protein and was higher than the control and the commercial product. The food also contained nutrition as required by the Indonesian National Standard (SNI) and Food and Agriculture Organization (FAO) standard. Furthermore, the functional properties of the infant food was comparable to that of the commercial and control product.